Estudo dos efeitos das ressecções colônicas parciais em ratos - Fernandez, Pedro Muñoz (1999)
In order to study the effects of partial colectomy, 30 rats Wistar were divided into three groups: GI and GII had the cecun and the ileo cecal valve resected and proximal colectomy was performed in GI and distal in GII. GIII had distal colectomy without cecum resection. The length of the remain colon was of 5 cm in all groups. Colostomy was performed in GI , GII and GIII. Parameters evaluated: body weight, fecal composition concerning to water, lipids and proteins on preoperative time and on the 10th, 20th, 30th, 40th, 50th and 60th days of postoperative time. All statistical tests were conducted at a 5% two-sided risk level. The evaluation was made by analysis of variance techniques. Conclusions: Concerning to body weight, there is no significant difference on the late postoperative time in any group or when comparing the three groups on this same period. On late postoperative time, GI and GII had a large amount of fecal water, lipids and proteins when compared to the preoperative time and to GIII. On the 60th day there's no significant difference on the quantity of fecal water when comparing the three groups and the same occurs on the 50th day when considering the quantity of fecal proteins.